2005
DOI: 10.1002/app.22329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organoclay on the thermal stability, mechanical strength, and surface wettability of injection‐molded ABS–clay nanocomposite materials prepared by melt intercalation

Abstract: ABSTRACT:In this article, a series of polymer-clay nanocomposite (PCN) materials consisted of commercial thermoplastic ABS matrix and dispersing inorganic organoclay platelets were successfully prepared by melt intercalation through the twin-roller mixer. The as-prepared materials in the form of pellet were then shaped by injection-molding machine and the as-molded specimens were subsequently examined by chemical characterizations, through Fourier transformation infrared (FTIR) spectroscopy, powder X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…They obtained qualitative and quantitative indications about the degree of the water and oil repellency and of the surface free energy of the grafted surface. Yeh et al studied the contact angle behaviour of the Acrylonitrile butadiene styrene (ABS) clay nanocomposites very recently [16]. Contact angle of water on the ABS-clay nanocomposite materials increased with respect to the increase in clay content.…”
Section: Introductionmentioning
confidence: 99%
“…They obtained qualitative and quantitative indications about the degree of the water and oil repellency and of the surface free energy of the grafted surface. Yeh et al studied the contact angle behaviour of the Acrylonitrile butadiene styrene (ABS) clay nanocomposites very recently [16]. Contact angle of water on the ABS-clay nanocomposite materials increased with respect to the increase in clay content.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that this effect may be due to surface enrichment and molecular assembly of nanostructures bearing low surface energy alkyl groups. Yeh et al [28] also reported higher surface hydrophobicity of organoclay filled acrylonitrile-butadiene-styrene nanocomposites. Deng et al [29] and Song et al [30] showed enhanced hydrophobicity and lower surface energy of organo-MMT modified polyurethane nanocomposites.…”
Section: Introductionmentioning
confidence: 90%
“…However, for some clays, increased MMT content resulted in a slight increase of yield strength. Yeh et al, 2006 found that the incorporation of organoclay platelets into polymer matrix increased the tensile strength of ABS for concentrations up to 3 wt %. Further amounts of organoclay loading (e.g.…”
Section: Tensile Testmentioning
confidence: 97%
“…Finally, the char residue increases to about 0.7%, which is obviously a result of the incorporation of the inorganic clay that remains as residue and contributes to the final weight (Table 3). It should be noted that, TGA studies of Yeh et al, 2006 made with ABS nanocomposites in air, have also shown an enhancement of thermal stability as well as an increase of the remaining residue. Similarly, Patiño-Soto et al, 2007 observed that dispersed clay enhances the thermal stability of ABS, since the intercalated or exfoliated clays display barrier properties against the diffusion of atmospheric oxygen into the material, inhibiting oxidative attack of the system.…”
Section: Tgamentioning
confidence: 99%
See 1 more Smart Citation